1990
DOI: 10.1021/ma00221a006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient evaluation of poly(oxyethylene) complex formation with alkali-metal cations

Abstract: An efficient method is developed for the evaluation of the complexation of poly-(oxyethylenes) (POE) with alkali-metal cations in solution. Equations derived from equilibria controlling the chromatographic retention allow us to determine the complex formation constants of a variety of POE oligomers contained in polydisperse POE samples. Statistical consideration shows that compounds having less than 16 repeating oxyethylene (EO) units form only 1:1 complexes whereas those having more than 17 EO units form 1:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 4 publications
3
36
0
Order By: Relevance
“…65 In the separation sciences, polyethers have been mainly used for the separation of cations, while very little attention has been paid to the separation of polyethers themselves. It has been reported that the chromatographic separation of polyethers provides very useful information on the solution behaviors of polyethers [66][67][68][69][70] , which cannot be elucidated by other methods.…”
Section: ·4 Polyether Complexation At the Surface Of Ion-exchange Rementioning
confidence: 99%
“…65 In the separation sciences, polyethers have been mainly used for the separation of cations, while very little attention has been paid to the separation of polyethers themselves. It has been reported that the chromatographic separation of polyethers provides very useful information on the solution behaviors of polyethers [66][67][68][69][70] , which cannot be elucidated by other methods.…”
Section: ·4 Polyether Complexation At the Surface Of Ion-exchange Rementioning
confidence: 99%
“…Other applications, such as protein extraction, oil recovery as well as metal cation extraction, have also been reported [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For investigating polyether complexation, we have developed efficient means based on separation techniques, such as cation-exchange chromatography [19][20][21][22] , anion-exchange chromatography 23,24 , and capillary electrophoresis. 25 These methods have permitted us to elucidate polyether chemistry, which is difficult to study with conventional spectrometric, electrochemical, and thermodynamic methods.…”
mentioning
confidence: 99%